Adaptation of the disease-related apathy scale in adults with epilepsy into Turkish: A methodological study - Turan, Gulcan Bahcecioglu; Ozer, Zulfunaz; Basak, Seda (Wiley, 2025)
ObjectiveThis study was conducted to culturally adapt the Epilepsy-Related Apathy Scale in Adults with Epilepsy (E-RAS) to Turkish and to assess its psychometric properties in adult epilepsy patients. MethodsA total of 172 epilepsy patients receiving care at the Neurology clinic and outpatient clinic of F & imath;rat University Hospital from February to July 2023 were included in this methodological investigation. The E-RAS was translated into Turkish, and its content and construct validity were thoroughly examined. Construct validity was assessed through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Reliability was evaluated through item analyses, internal consistency analysis, composite reliability coefficient, and mean explained variance analysis. ResultsThe factor loadings of the scale items ranged from 0.66 to 0.89. The fit index values of the scale were X-2 = 467.09, df = 245 (p <0.05), X-2/df = 1.9, RMSEA = 0.073, CFI = 0.97, RMR = 0.046, SRMR = 0.057, TLI = 0.97, and AIC = 557.09. The Cronbach's alpha coefficients of the sub-dimensions of the scale ranged from 0.880 to 0.992, and the total Cronbach's alpha coefficient was 0.928. The total McDonald's omega coefficient was 0.916, and the McDonald's omega coefficients of the sub-dimensions ranged from 0.880 to 0.947. The Turkish form of the 24-item and 4-sub-dimensional scale was validated without any changes to the original scale form. SignificanceThe Turkish adaptation of E-RAS is a valid and reliable instrument for measuring apathy in adult epilepsy patients. Its use in clinical practice is strongly recommended. Plain Language SummaryThe E-RAS scale can be used to assess apathy in adults with epilepsy. The was determined that the adapted Turkish form had a similar structure to the original scale. It was determined that the E-RAS scale is valid and reliable in Turkish culture. The fact that the Turkish adaptation of the scale is similar to the original structure and other adapted cultures is a factor that facilitates its use and acceptance in international comparisons. The scale can be used to assess apathy in adults with epilepsy.
Keywords: adaptation; apathy; epilepsy; patient; psychometric properties